A review on scheduling schemes of high speed wireless campus network for Interactive Multimedia transmission - Alam, Md. Khorshed; Abd Latif, Suhaimi; Masud , Mosharrof Hussain; Anwar, Farhat (2013)
Interactive Multimedia (IMM) offers voice, video conferencing, graphics services at low cost with more flexibility in a high speed Wireless Local Area Network (WLAN) that can be defined as a high speed Wireless Campus Network (WCN). In a video or voice conversation, the direction of traffic flow over the networks defines the participating users work either as a sender or a receiver. In order to improve performance of IMM traffic in WCN, data loss has to be kept minimum with maximum throughput. Packets scheduling is one of the challenging issues for improving IMM transmission and it is still an unresolved problem over WCN. This work aims to explain the fundamental characteristics of IMM related to various applications and highlights the present scheduler issues. A new scheduling scheme has been proposed which is expected to deliver the optimum Quality of Service (QoS) with the least handoff delay and call dropping probabilities for IMM applications though WCNs